The effect of social exclusion on aggressive behavior among Chinese college students: the mediating role of relative deprivation and the moderating role of upward social comparison - Yu, Xiaofang; Xiao, Gensen; Zhang, Yanzhen (Frontiers in Public Health, 2025)
BackgroundThe current study examined the effect of social exclusion on aggressive behavior, how relative deprivation might mediate this effect, and how upward social comparison (USC) might moderate the indirect pathway.MethodsOne thousand seven hundred and sixty-six college students were investigated, with an average age of 19.53 (SD = 1.09) years. Participants completed questionnaires regarding social exclusion, aggressive behavior, relative deprivation, and USC. The data was analyzed using regression-based moderated mediation modeling. PROCESS Models 4 and 7 macros for SPSS were used to test the mediation and moderated mediation models with 5,000 random sample bootstrapping confidence intervals (CIs).ResultsThe findings revealed a significant positive association between social exclusion and aggressive behavior among Chinese college students (r = 0.362, p < 0.001). Relative deprivation played a partial mediating role between social exclusion and aggressive behavior (indirect effect = 0.045, 95%CI [0.028, 0.062]). The association between social exclusion and aggressive behavior was moderated by USC. For college students with low USC, the effect of moderated mediation (effect = 0.035, 95%CI [0.022, 0.050]). For college students with high USC, the effect of moderated mediation was 0.057 (95%CI [0.034, 0.081]). The link between social exclusion and relative deprivation was stronger for college students with high levels of upward social comparison than for college students with low levels of upward social comparison (β = 0.405, t = 11.976, p < 0.001 vs. β = 0.251, t = 8.182, p < 0.001).ConclusionRelative deprivation could be a mechanism by which social exclusion was linked with aggressive behavior and USC enhanced the effect of relative deprivation. This study was important in investigating how social exclusion was related to aggressive behavior among Chinese college students which provided meaningful implications for reducing aggressive behavior. Thus, this study explored “how” and “when” social exclusion might enhance aggressive behavior among Chinese college students. The results suggested that relative deprivation and USC might be prime targets for prevention and intervention programs of aggressive behavior among Chinese college students.